Characteristics of Sucrose Transport through the Sucrose-Specific Porin ScrY Studied by Molecular Dynamics Simulations - Sun, Liping; Bertelshofer, Franziska; Greiner, Günther; Böckmann, Rainer A. (Frontiers in Bioengineering and Biotechnology, 2016)
Sucrose-specific porin (ScrY) is a transmembrane protein that allows for the uptake of sucrose under growth-limiting conditions. The crystal structure of ScrY was resolved before by X-ray crystallography, both in its uncomplexed form and with bound sucrose. However, little is known about the molecular characteristics of the transport mechanism of ScrY. To date, there has not yet been any clear demonstration for sucrose transport through the ScrY. Here, the dynamics of the ScrY trimer embedded in a phospholipid bilayer as well as the characteristics of sucrose translocation were investigated by means of atomistic molecular dynamics (MD) simulations. The potential of mean force (PMF) for sucrose translocation through the pore showed two main energy barriers within the constriction region of ScrY. Energy decomposition allowed to pinpoint three aspartic acids as key residues opposing the passage of sucrose, all located within the L3 loop. Mutation of two aspartic acids to uncharged residues resulted in an accordingly modified electrostatics and decreased PMF barrier. The chosen methodology and results will aid in the design of porins with modified transport specificities.